Autism in DSM-5-TR, what has changed? (Research, Society and Development, 2024)
The nosology of Autism Spectrum Disorder (ASD) is historically very recent, having first appeared as a category of its own in 1980, and was previously considered to be a type of childhood schizophrenia. Autism is now understood as a neurodevelopmental condition whose most striking characteristic is a persistent deficit in communication and social interaction skills, affecting 1 in 36 children, according to the CDC. The most widely accepted definition and criteria for the disorder rest on the main manuals, namely the Diagnostic and Statistical Manual of Mental Disorders (DSM) and the International Code of Diseases (ICD), which seek to adapt to new scientific and socio-cultural updates, with the aim of making diagnostic models clearer and more reliable. In 2022, the revision of the fifth edition of the DSM (DSM-5-TR) was published, which led to some changes regarding both the criteria and the wording of the condition for ASD.  In this sense, the aim of this article is to present a study of the changes brought about by the DSM-5-TR in the category of ASD, as well as to discuss the contexts and reasons behind these changes.